Ownership Structure as a Resilience Moderator: Phase-Dependent Asymmetric Drawdown Dynamics in Blue-Chip Versus Broad-Market Indices During a Geopolitical Crisis - Muchammad Bachtiar; Fithriyyah Shalihati; Agustina Widi Palupiningrum; Anny Ratnawati (AI, Big Data and Quantitative Methods in Finance, 2026)
Background: Geopolitical armed-conflict events generate severe multi-phase disruptions in emerging market equity markets. When concentrated foreign institutional ownership characterises the blue-chip segment, a structural outflow paradox may invert the classical flight-to-quality prediction, rendering fundamentally stronger equities the preferred vehicle for programmatic capital exit.Purpose: This study investigates whether concentrated foreign ownership in LQ45 generates a systematic flight-to-quality inversion across three phases of the 2026 Iran-Israel-US geopolitical crisis on the Indonesia Stock Exchange.Design/methodology/approach: Maximum Drawdown and Cumulative Return are calculated from daily closing prices (n = 24 trading days) for LQ45 and the Jakarta Composite Index across three crisis clusters: K1 Initial Panic, K2 Energy Crisis, and K3 Resolution and Recovery, employing multi-cluster phase analysis to reject the temporal homogeneity assumption of single-window event studies.Findings/Result: LQ45 underperforms IHSG on Cumulative Return across all clusters, with the differential widening from 0,89 to 2,27 percentage points. The K1-to-K2 Maximum Drawdown reversal confirms that foreign rebalancing concentrates selling pressure on the most liquid segment. The K3 asymmetry (IHSG: +2,02%; LQ45: -0,25%) reflects the advantage of a domestically anchored investor base in capturing de-escalation signals.Conclusion: These findings introduce the Phase-Dependent Asymmetric Resilience Model (PDARM) as a conditional framework for predicting flight-to-quality inversion in ownership-heterogeneous emerging markets, with implications for portfolio allocation and market stabilisation.Originality/value (State of the art): This study is the first intra-exchange, multi-phase characterisation of the 2026 Middle East crisis on the Indonesia Stock Exchange, showing that ownership-driven resilience asymmetry is measurable within a single exchange under identical shock conditions. Keywords:geopolitical risk, capital outflow, market resilience, emerging markets, Indonesia Stock Exchange